Kajian status sosial kanak-kanak keperluan khas di Sarawak dan Kelantan - Rasidah Abd Wahab; Haironi Yusoff; Hashami Bohari; Norizan A. Majid; Wan Asma Wan Ismail; Kamaruzaman Che Su (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
The objectives of this study are to determine the social status of children with special needs in Kelantan and Sarawak and to identify the association of social status with study area, gender and diagnosis. The study involved 103 new cases children aged 6 to 18 years old. There are 67 (65% ) males and 36 ( 35% ) females and by diagnosis;26 ( 25.2% ) are Down’s Syndrome, 11 ( 10.7% ) are Cerebral Palsy while 66 (64.1% ) are Mental Retardation. The caretaker or the health personnel on each children completed a Quality Of Life questionnaire. The questions include 4 aspects ; (i) Problem in playing with friends, (ii) problem of sharing toys, (iii) problem of following instruction and (iv) take-turn problem. By associating the problems with gender, study area and diagnosis; there is a significant association between the problem of sharing toys, following instruction and take-turn with study area. Most of children from Sarawak; 44.8% are having problem in sharing toys compared to 14.9% children from Kelantan ( p<0.05 ); while 34.5% children’s from encountered problem in following instruction compared to Kelantan ( p<.05) and 37.9% children from Sarawak having take-turn problem compared to 13.5% children’s from Kelantan ( p<.05). There was no significant association between gender, study area and diagnosis with problem of playing with friends. The finding indicate that a special attention and a good intervention programme should be conducted in order to overcome the problems.